Caracterização e predição de genitores visando à tolerância a germinação na pré-colheita em trigo (Triticum aestivum L.) - Nörnberg, Rafael (2012)
The climate adversities, such as high temperatures and rain before and during the harvesting period lead to a phenomenon called Pre-harvest sprouting (PHS) of wheat grain. This germination decreases the wheat flour quality through the activation of enzymes responsible for germination which degrade starch. Therefore, this study had as objective to analyse the character pre-harvest sprouting in hexaploid wheat genotypes (Triticum aestivum L.), in the Southern region of Brazil, based on distinct evaluation years. Also, the evaluations aim to indicate the most adapted cultivars for Southern Brazil and to select parental genotypes for breeding programs of wheat. The experiment was conducted in the years 2010 and 2011, in the Centro de Genômica e Fitomelhoramento, Faculdade de Agronomia Eliseu Maciel, Universidade Federal de Pelotas (CGF/FAEM/UFPel), located at Capão do Leão County/RS, Brazil. The design used was random blocks with three replications. A total of 33 genotypes were phenotyped regarding agronomic and pre-harvest sprouting characters in wheat. Simultaneously, in 2010, 56 F1 and F2 hybrid populations obtained from artificial hybridizations between eight wheat cultivars, with different tolerance to sprouting according to a complete diallel design, with reciprocals. The populations and their parental genotypes were evaluated in the agricultural season of 2011. In this experiment, the following characters were evaluated: percentage of germinated grains (GG) in the fixed generations F1 and parents, falling number index (FNI) in the fixed generations F1 and parents, and segregant populations (F2). In the analysis of genotype x year, it was detected an interference of the environment on the results of some genotypes. The genotypes: BIO 08228, RAÍZES, HORIZONTE and BRS 194 with the lowest GG values, and the cultivar GUAMIRIM with high FNI, for both evaluation years, showing the presence of PHS tolerance alleles. Based on the genetic dissimilarity, was obtained from the prediction of important parents. Thus elite genotypes such as TBIO ITAIPÚ, BIO 08228, RAÍZES, HORIZONTE, BRS 194, TBIO PIONEIRO, BIO 07367, RAÍZES, GUAMIRIM and FRONTANA were obtained to form the crossing blocks, aiming to complement the distinct alleles for PHS. The majority of genotypes presented reduced alpha-amylase activity, which causes starch degradation. The genotypes TBIO PIONEIRO, MARFIM and TBIO TIBAGI, on the other hand, presented the lowest alpha-amylase activity. There was a high heritability for both characters in both years except for GG of susceptible genotypes in 2011. The PHS tolerance is controlled by additive effects of genes evidenced by high general combining ability and by non-additive effects of genes evidenced by the specific combining ability, but it was evident that the additive effects were more important. The cultivars QUARTZO and FRONTANA presented the best potential for the use in crossing blocks aiming to increase PHS tolerance and to reduce alpha-amylase activity. Transgressive segregation was observed with high heterosis estimates for both traits FNI and GG. This, added to the loss of vigor by inbreeding for FNI, this indicates that these combinations are potential sources of tolerance to PHS. There was a high reciprocal effect that should be taken into account when producing hybrid cultivars with tolerance to pre-harvest germination and high FNI.